Health Insurance and Long-Term Care Services for the Disabled Elderly in China: Based on CHARLS Data - Chen L; Zhang X; Xu X (Dove Medical Press, 2020)
Linhong Chen, 1, 2 Xiaolu Zhang, 3 Xiaocang Xu 4 1Department of Applied Statistics, School of Mathematics and Statistics, Chongqing Technology and Business University, Chongqing 400067, People’s Republic of China; 2Department of Public Administration, School of Public Administration, Sichuan University, Chengdu 610065, People’s Republic of China; 3Department of Trade Economics, School of Economics, Chongqing Technology and Business University, Chongqing 400067, People’s Republic of China; 4Department of Economics, Research Center for Economy of Upper Reaches of the Yangtse River/School of Economics, Chongqing Technology and Business University, Chongqing 400067, People’s Republic of ChinaCorrespondence: Xiaocang XuResearch Center for Economy of Upper Reaches of the Yangtse River/School of Economics, Chongqing Technology and Business University, Chongqing 400067, People’s Republic of ChinaTel +86-15178882448Fax +86-023-62769376Email cangxiaoxu@ctbu.edu.cnPurpose: This paper aimed to explore the relationship between the different factors, especially health insurance, and the availability of long-term care (LTC) services, among the disabled elderly.Methods: Based on the data of China Health and Retirement Longitudinal Study (CHARLS), the logistic regression model was utilized to evaluate the influence of the different factors, especially health insurance, on the availability of long-term care services.Results: Our findings show some interesting results. Firstly, the findings suggest that informal long-term care (LTC) services for elderly persons with disabilities heavily depend on a family member from different health insurance groups. About 80.733% of the disabled elderly depend on a family member as their primary caregivers. Secondly, other influence factors such as income and area of residence were also significantly related to the availability of long-term rental services. Thirdly, Health insurance is a very important factor influencing the availability of Long-term care services both in urban and rural areas (p< 0.001) but Income is the most interesting variable.Conclusion: Based on our results, the growth and integration of formal long-term care (LTC) services should be facilitated. Firstly, policymakers can encourage formal long-term care (LTC) services from a variety of sources to work together to increase overall supply capability. Secondly, the long-term living security needs of people who do not have health insurance should be regulated through subsidies according to the economic status.Keywords: long-term care, LTC, the disabled elderly, health insurance, CHARLS data, informal care, formal care